MARKETING MIX IN THE BEEF RETAIL - Medeiros, Haroldo de Sá; Paes-de-Souza, Mariluce; Souza Filho, Theophilo Alves de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This article aims to analyze the value perception of fresh beef buyers from marketing mix considered by customers in the buying process companies in the supermarket segment of Porto Velho-RO, aiming at proposing a model of marketing mix targeted at retail beef. To this, were analyzed the perception of value buyers of beef and acquaintances which elements of the retail marketing mix were considered upon purchase. Furthermore, we analyzed which elements influence the buying behavior of consumers. The methodology used in this study is qualitative- quantitative and the approach is descriptive. The data collection occurred through questionnaires given to 316 people. In order to meet the objective , the method used was the factorial analysis . The underlying structure retail marketing mix, when it is related to marketing of beef, was found. These structures are given for eight factors, which are: communication, attendance, access , price, product , hygiene and decoration, layout and consistency.